2021
DOI: 10.1371/journal.pone.0249570
|View full text |Cite
|
Sign up to set email alerts
|

Heparin binding protein in severe COVID-19—A prospective observational cohort study

Abstract: Background and aims Neutrophil-derived heparin binding protein (HBP; also known as azurocidin or CAP-37) is a key player in bacterial sepsis and a promising biomarker in severe infections. The aims of this study were to assess whether HBP is involved in the pathophysiology of COVID-19 and, if so, whether it can be used to predict severe disease preferably using a point-of-care test. Methods This was a prospective convenience sample study of biomarkers in patients admitted to Skåne University hospital in Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…In clinical studies, neutrophilderived HBP levels were significantly increased in COVID-19 patients who developed organ failure compared with those in patients who did not. These results suggest that HBP levels can predict the development of organ dysfunction caused by COVID-19 [243].…”
Section: Advantages Disadvantages and Clinical Applications Of Antimi...mentioning
confidence: 67%
“…In clinical studies, neutrophilderived HBP levels were significantly increased in COVID-19 patients who developed organ failure compared with those in patients who did not. These results suggest that HBP levels can predict the development of organ dysfunction caused by COVID-19 [243].…”
Section: Advantages Disadvantages and Clinical Applications Of Antimi...mentioning
confidence: 67%
“…HBP is also associated with other critically ill conditions, including acute kidney injury (AKI), acute respiratory distress syndrome (ARDS), and acute bacterial meningitis [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, a recent study has reported that HBP concentration increased prior to organ dysfunction in patients with severe coronavirus disease (COVID-19) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, HBP concentration has been measured using a non-automated ELISA [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. An ELISA is a simple and easy procedure to perform, and shows high sensitivity and specificity; it is, however, labor-intensive, has a high possibility of false positive and false negative, and shows antibody instability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence regarding heparin-binding protein (HBP) increase in COVID-19 is not sufficient until these days, while there are a limited number of studies discussing this phenomenon [ [2] , [3] , [4] ]. In order to fully understand the potential role of HBP in pathophysiology of COVID-19 infection, more clinical studies are needed.…”
mentioning
confidence: 99%